Functions of Oxysterol-Binding Proteins at Membrane Contact Sites and Their Control by Phosphoinositide Metabolism - Nakatsu, Fubito; Kawasaki, Asami (Frontiers in Cell and Developmental Biology, 2021)
Lipids must be correctly transported within the cell to the right place at the right time in order to be fully functional. Non-vesicular lipid transport is mediated by so-called lipid transfer proteins (LTPs), which contain a hydrophobic cavity that sequesters lipid molecules. Oxysterol-binding protein (OSBP)-related proteins (ORPs) are a family of LTPs known to harbor lipid ligands, such as cholesterol and phospholipids. ORPs act as a sensor or transporter of those lipid ligands at membrane contact sites (MCSs) where two different cellular membranes are closely apposed. In particular, a characteristic functional property of ORPs is their role as a lipid exchanger. ORPs mediate counter-directional transport of two different lipid ligands at MCSs. Several but not all ORPs transport their lipid ligand from the ER in exchange for phosphatidylinositol 4-phosphate (PI4P), the other ligand, on apposed membranes. This ORP-mediated lipid “countertransport” is driven by the concentration gradient of PI4P between membranes, which is generated by its kinases and phosphatases. In this review, we will discuss how ORP function is tightly coupled to metabolism of phosphoinositides such as PI4P. Recent progress on the role of ORP-mediated lipid transport/countertransport at multiple MCSs in cellular functions will be also discussed.